Effect of Pharmacist Participation in an Antimicrobial Stewardship Program on the Appropriateness of Antibiotic Use in the Inpatient Department at Sungaikolok Hospital - Pimapansri, Supawadee; Tanchaitechawut, Tatchai (Princess of Naradhiwas University Journal, 2025)
Background and Objectives Pharmacists play a major role in monitoring, evaluating, and intervening in antimicrobial prescribing as part of the Antimicrobial Stewardship Program (ASP). This study aimed to assess the impact of pharmacist involvement in the ASP on the appropriateness of antimicrobial prescribing in the inpatient department at Sungaikolok Hospital. Methods A retrospective study was conducted by reviewing prescription records to compare both the appropriateness and the volume of antimicrobial use during periods with and without pharmacist participation. The study focused on five key antimicrobial agents: Meropenem, Piperacillin/ Tazobactam, Vancomycin, Colistin, and Cefoperazone/ Sulbactam. A total of 506 prescriptions were analyzed. Results The appropriateness of antimicrobial prescribing significantly decreased during the period with pharmacist involvement compared to the period without (16.7% vs. 8.8%, P-value < 0.001). Most inappropriate prescriptions were due to incorrect dosages (7.7%) and inappropriate indications (5.9%). Pharmacists provided recommendations regarding antimicrobial use to physicians, all of which (100%) were accepted and led to modifications in prescribing. When comparing the volume of antimicrobial use, only Meropenem showed a statistically significant increase during the pharmacist-involved period (14.7 ± 4.3 vs. 5.0 ± 0.5; P-value < 0.001). The consumption of most other antimicrobials did not differ significantly. Conclusion and Recommendations Pharmacist involvement in the Antimicrobial Stewardship Program supports the provision of recommendations to physicians, especially regarding dosing, which enhances the appropriateness of antimicrobial prescribing. However, most antimicrobial consumption did not show a statistically significant difference. It is recommended that pharmacists participation in ASP be continued to further improve antimicrobial use and patient outcomes.